Study on torsional vibration characteristics of compressor flexible rotors considering contact clearance - HUANG Zhiqiang; WANG Jie; LI Tao; LI Gang; WANG Shuo; MU Dequan (Jixie qiangdu)
The torsional vibration of reciprocating compressor crankshaft system can cause major problems such as burnt bearings and shaft fracture.In order to understand the torsional vibration response of the compressor rotor system, a torsional vibration mechanics solution method for the flexible rotor system of the compressor considering the bushing-pin collision clearance and the oil film clearance of the crankshaft-bearing was proposed, which provided a new idea and method to avoid the natural frequency of the crankshaft system.Based on the multi-body dynamics and Hertz contact theory，the torsional dynamic response of the crankshaft system with collision clearance was solved.The results show that the torsional vibration amplitude of the 4th column crank pin is the largest, the torsional angular displacement amplitude is 0.051°, and the dynamic angular velocity peak value is 156.026 rad/s.Based on this, the crankshaft-bearing oil film clearance was considered, the oil film pressure of sliding bearings was calculated by the finite difference method and the over-relaxation iterative method, and the dynamic characteristic coefficients of bearings were solved according to pressure perturbation method.The effects of the bushing-pin collision clearance and the crankshaft-bearing oil film clearance on the dynamic response of the crankshaft system were comprehensively considered in the modal analysis of the crankshaft system under preload.The resonance of the crankshaft with and without oil film clearances was compared. The results show that the natural frequencies of the 3rd and 8th orders of the crankshaft system decreases by 44.64% and 21.23%, and when considering the reduction of the resonant speed point of the crankshaft with comprehensive clearance in the same speed range, the 2nd order critical speed is reduced by 38.55%, and the probability of resonance increases.